Storms - Canizares, Susan (New York : Scholastic, 1998)
Photographs and simple text describe what happens when there is too much rain, wind, or snow.
"Scholastic early childhood"--Includes index
Keywords: Storms -- Juvenile literature; Rain and rainfall; Winds -- Juvenile literature; Snow -- Juvenile literature